Effects of deltamethrin on primordial germ cells of zebrafish (Danio rerio) embryos - (:unkn) unknown (My University, 2013)
In sexually reproducing organisms, primordial germ cells (PGCs) give rise to the cells of the germ line, the gametes. In many animals, PGCs are set apart from somatic cells early during embryogenesis. This study explores the effects of deltamethrin on primordial germ cells (PGCs) of the zebrafish embryos, and examines their morphology during early development (1st-15 th day). Different doses of deltamethrin gave to the medium of zebrafish embryos and effects of this pesticide on primordial germ cell structure and migration were detected with histological stainings. PGCs have been selectively stained by the alkaline phosphatase histochemical reaction and viewed by light microscopy from the time they are first detectable in the yolk sac endoderm. PGCs moved to between blastoderm and yolk sac, and were transferred to the dorsal mezentery where they formed gonadal anlage with mesodermal cells. PGCs were easily distinguished from somatic cells by their morphology and their distinct cytoplasmic membrane.
Keywords: Deltamethrin; Embryo; Histology; Primordial germ cell; Zebrafish